Analisa Aliran Daya Sistem Distribusi Kelistrikan Pada Gedung PT. X - Ikhsan Priyambudi, Ghani; Abdul Rozak, Ojak (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2025)
The 3-phase, balanced electrical system is always solved per phase and displayed in a line diagram that matches the system. The purpose of the line diagram is to provide all the information you need. In various cases, the diagram will vary depending on the problem being solved. The use of technology in this project is the analysis of the power process from the Mega Watt (MV) distribution field, transformers, and low voltage electrical distribution systems. The purpose of this study is to measure the distribution of electrical output from the MV panel to both transformers to reduce the voltage from 60 kV to 380 volts and calculate the transformer voltage that comes from 20 kV to 380 volts or 400 volts. The amount of imbalance and stability results are less than 3%, as a result of the measurement stability results of 0.2% on the panel curve containing and 0.25% on the tension of the outgoing PUTR panel. The value of imbalance and electrical stability results from the PUTR 1.66% output panel is 2.97% and at PUTR 2 is 4.66%. To ensure that the imbalance is below 5%.